Black and Blue: how democratic attitudes shape affect toward Blue or Black Lives Matter - Vitriol, Joseph A.; Sandor, Joseph; Farhart, Christina E. (Frontiers in Social Psychology, 2024)
In the context of longstanding racial discrimination within the legal system, high-profile incidents of police violence and misconduct have recently precipitated widespread collective action among members of marginalized communities. A large body of evidence demonstrates that social movements like Black Lives Matter, which were organized in response to legitimate concerns about racial inequality and discrimination in the legal system, have led to increased political participation, egalitarian racial attitudes, and policy reform. Still, much is unknown about the factors that shape public perceptions of Black Lives Matter; even less is known about factors influencing public opinion toward Blue Lives Matter—a movement concerned with the safety of the law enforcement community, and which may also provide ideological defense against the claims and demands of Black Lives Matter and in support of police officers believed to be unfairly maligned. Using data from two panel studies, including one sampled to approximate national representativeness, we demonstrate that positive affect toward Black Lives Matter covaries with pro-democratic attitudes and legal forms of social protest, and the belief that one's behavior can precipitate meaningful political change. We also demonstrate that anti-democratic attitudes, more satisfaction with democracy, and increased trust in government predict positive affect toward Blue Lives Matter. These results emerge while controlling for ideological self-placement and demographic variables, as well as political interest and knowledge. We discuss these findings in light of perspectives on collective action and social movement, intergroup conflict and prejudice, and ideological differences in support of democratic norms and values.